Capturing changes: applying the Oxford system to further understand the movement of metal in Shang China - Liu, R (2016)
The Bronze Age China presents to us a significant contrast to the rest of Eurasia in two aspects, the great commitment to the complicated bronze ritual vessels and the immense scale of production. Both features reached their zenith in the late Shang period in the late second millennium BC but left a delicate puzzle to archaeologists: through what trajectories was the metal moved and engaged with human societies in China? The traditional approach is heavily confined to either cultural-historic paradigms or text-oriented researches. Whilst the increasing number of scientific studies in recent decades allows scholars to be more precisely focused on bronze artefacts, their sometimes overwhelming obsession on the provenance of metal provokes criticism in many ways. Drawing from approximately 3000 alloying analyses, 1000 trace elemental data and 1100 lead isotopes, this thesis delivers a series of systematic comparative studies on copper-based artefacts with the newly developed Oxford system. The waning and waxing of various types of metal in different time and space depict a constantly and unpredictably changing pattern. People inhabited along the borderlands appeared to be greatly dependent on local supply of metal whereas Anyang undoubtedly absorbed metal from a variety of regions. Intriguingly, seen from the current database, very little evidence can be highlighted in support of some large-scale mixing or recycling, particularly for ritual vessels of top elites at Anyang. The newly discovered compositional difference of bronzes between Zhengzhou and Panlongcheng calls into question on the classical model on the relation between the two sites. Striking domination of clean copper in southwestern China shed new light on the issues of local production and local supply of metal. In conclusion, the chemical and isotopic analyses of copper-based objects carry a huge amount of information not just on provenance but many others. People living in various parts of China had chosen differing strategies to obtain metal. The elaborate data structures are a result of a highly efficient and dynamic network supplying system. Through combining the changes in metal compositions with other archaeological information, it becomes viable to reveal more subtle knowledge about this remote world and give us better-defined questions.